The elucidated Consent: Contributions from the “Psy” Domain to the Current Clinical Practice - Rovaletti, María Lucrecia (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2014)
This work tries to show how autonomy principle can turn ethos of health agent and, with it, of contemporary practices. This principle leave aside paternalistic moral. In that, “professional criterion” decides information to know and it leads to autonomous moral of reasonable person where individuals play an active role in made of social order. “Autonomy” should be understood focused on a more peripheral level of “choices” and “autonomous actions”, considering subject competence according to minimum, medium and maximum levels (Drane). Psychodynamic psychology has helped to humanize dyadic relationships where the unconscious plays an important role such as those linking patient to therapist, client to professional and subject to researcher. Thus, the application to them of psychoanalytic mechanisms such as transference and countertransference can illuminate their nature and help to resolve any negative transference that may be obstructing their dialogical space.